2019
DOI: 10.7166/30-3-2235
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Four Qualities of Intelligent Industrial Reporting

Abstract: Internationally, innovation and technology are driving change through concepts such as 'Industry 4.0'. However, due to various constraints, South Africa is lagging behind in this transformation. Furthermore, local industry generates large amounts of data that could contribute to a positive transformation. Data analytics, in the form of reporting, may therefore present a workable alternative to understand better the intricate nature of real-world operations. This paper identifies four qualities for the practica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Mining Industry 1- Botes et al (2019) identified four qualities, namely, establishing a focus area, data availability, analytics and visualization, that contributed to intelligent reporting, and applied them to a case study to evaluate the current intelligence of the reporting of the case study and areas for improvement based on data-driven decision-making.…”
Section: Allmentioning
confidence: 99%
“…Mining Industry 1- Botes et al (2019) identified four qualities, namely, establishing a focus area, data availability, analytics and visualization, that contributed to intelligent reporting, and applied them to a case study to evaluate the current intelligence of the reporting of the case study and areas for improvement based on data-driven decision-making.…”
Section: Allmentioning
confidence: 99%
“…Organisations operating in the contemporary business environment are moving towards using data to improve decision-making [10]. However, many industries use only a portion of the available data [11], which highlights the scope for a data-driven approach to managing commodities.…”
Section: Role Of Data In Decision-makingmentioning
confidence: 99%
“…Tools are often used, but only to generate a single dashboard or report [15]- [20]. Other studies focus on how to design an effective report or dashboard or how to measure its effectiveness [25], [26].…”
Section: Large-scale Implementationmentioning
confidence: 99%